2021
DOI: 10.1002/admt.202100920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Aspect Ratio on Stiffness and Conductivity in Phase‐Changing Particulate Composites

Abstract: Variable stiffness in elastomers can be achieved through the introduction of low melting point alloy particles, such as Field's metal (FM), enabling on‐demand switchable elasticity and anisotropy in response to thermal stimulus. Because the FM particles are thermally transitioned between solid and liquid phases, it is beneficial for the composite to be electrically conductive so the stiffness may be controlled via direct Joule heating. While FM is highly conductive, spherical particles contribute to a high per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 45 publications
(55 reference statements)
0
20
0
Order By: Relevance
“…However, despite the high concentration of FM microparticles in the polymer matrix, the SMP (without GNPs) exhibits low electrical conductivity (18.2 S m −1 ) because of the difficulty in attaining the percolation threshold with spherical FM microparticles for sufficiently high electrical conductivity. [ 64 ] The addition of GNPs into the FM‐PDMS composite helps to form a rich electrical network. With GNP inclusion, we were able to lower the resistivity of the platform nearly 200 times through the creation of conductive pathways between spherical FM microparticles and GNPs (resistivity: 0.06 Ω × m in SMP (without GNPs) vs 2.8 × 10 −4 Ω × m in eSMP (with GNPs); Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the high concentration of FM microparticles in the polymer matrix, the SMP (without GNPs) exhibits low electrical conductivity (18.2 S m −1 ) because of the difficulty in attaining the percolation threshold with spherical FM microparticles for sufficiently high electrical conductivity. [ 64 ] The addition of GNPs into the FM‐PDMS composite helps to form a rich electrical network. With GNP inclusion, we were able to lower the resistivity of the platform nearly 200 times through the creation of conductive pathways between spherical FM microparticles and GNPs (resistivity: 0.06 Ω × m in SMP (without GNPs) vs 2.8 × 10 −4 Ω × m in eSMP (with GNPs); Figure 2f).…”
Section: Resultsmentioning
confidence: 99%
“…Thermally-conductive particles such as FM in variable-stiffness composites have already been demonstrated to have a positive impact in this regard, 23 and there is evidence that smaller particles 55 or a mixture of particle sizes 56 may be able to improve thermal conductivity further. Electrical conductivity in phase-changing composites is also an area of interest, and studies focused on filler shape 54 have shown that elongated particles can enable direct Joule heating, promoting improved integration into systems-level applications. These works, in conjunction with future explorations of different phase-changing filler and matrix materials, all serve to widen and clarify our understanding of the emerging use of inclusions to impart variable-stiffness behavior.…”
Section: Discussionmentioning
confidence: 99%
“…After decades of development, there have been many strategies proposed to achieve variable stiffness, including granular materials or laminar jamming structures, , fluid–polymer composites, , magnetorheological materials, electrorheological materials, , shape memory polymers, shape memory alloys, , liquid crystal elastomers, and low-melting-point alloys, which are desired in many technological fields such as soft robotics, medical devices, aerospace, , automotive industry, , and wearable electronics . However, most of these stimulus methods require bulky equipment that adds considerable design complexity, weight, and cost to engineered systems, , which limit their application.…”
Section: Introductionmentioning
confidence: 99%